A Remark on the Regularity Criterion for the MHD Equations via Two Components in Morrey-Campanato Spaces. (25th June 2014) - Zhang, Zujin; Tang, Tong; Zhang, Fumin
Abstract : We consider the regularity criterion for the 3D MHD equations. It is proved that if the horizontal components of the velocity and magnetic fields satisfyu , b ∈ L 2 / ( 1 - r ) ( 0, T ; M ˙ 2, 3 / r ) with0 < r < 1, then the solution smooth. This improves the result given by Gala (2012).